The Constructivism English Online Teaching Moodle-Based Integration In Higher Education Context - Rizky Eka Prasetya (International Journal of English Linguistics, Literature, and Education (IJELLE), 2023)
The online environment has been transformed all educational contexts of Higher Education in Indonesia. This situation occurred because of the Covid-19 pandemic. The constructivism notion became undoubtful to be implemented in English pedagogy online Moodle environment. Nonetheless, there are a few investigations to the capabilities adopt and accept in Moodle system and specification feature. The study used a qualitative research approach ethnographic case study method to investigate an issue and get a thorough knowledge of constructivist philosophy in Moodle. The research focuses on 43 English lecturers in Higher Education in south Jakarta who are also transitioning to online instruction. A constructivist Moodle-based online environment was established using an electronic open-ended questionnaire and structured interview. The thematic analysis found the characterization of constructivism theory implements in Moodle-based. It included multiple resources material, engaging language learners’ experience, utilizing learners’ feedback, encouraging conversation, enhancing learners’ cognitive process, initiating learners’ autonomy environment, providing data and supplementary resources, and facilitating written interaction. The constructivism philosophy had been in integrating sufficiently in teaching English Moodle-based. The Resources and Activities had supported its features inside the system